In search of solidarity - Hope, K; Kofi N Hope (2012)
This thesis provides an account of the work of Canadian organizations that took part in the global anti-apartheid movement and then continued political advocacy work in South Africa post-1994. My central research question is: What explains the rise and fall of international solidarity movements? I answer this question by exploring the factors that allowed the Canadian anti-apartheid network to grow into an international solidarity movement and explaining how a change in these factors sent the network into a period of decline post-1994. I use two organizations, the United Church of Canada and CUSO, as case studies for my analysis. I argue that four factors were behind the growth of the Canadian solidarity network: the presence of large CSOs in Canada willing to become involved in solidarity work, the presence of radical spaces in these organizations from which activists could advocate for and carry out solidarity work, the frame resonance of the apartheid issue in Canada and the political incentives the apartheid state provided for South African activists to encourage Northern support. Post-1994 all of these factors shifted in ways that restricted the continuation of international solidarity work with South Africa. Accordingly I argue that the decline of the Canadian network was driven in part by specific South African factors, but was also connected to a more general stifling of the activist work of progressive Canadian CSOs over the 1990s. This reduction of capacity was driven by the ascent of neo-liberal policy in Canada and worldwide. Using examples from a wide swath of cases I outline this process and explain how all four factors drove the growth and decline of Canadian solidarity work towards South Africa.